Is the Growth of Small Firms Constrained by Internal Finance? - Carpenter, Robert E.; Petersen, Bruce C. (The Review of Economics and Statistics, 2002)
This paper examines the long-standing theory that the growth of small firms is often constrained by the quantity of internal finance. Under plausible assumptions, when financing constraints are binding, an additional dollar of internal finance should generate slightly more than an additional dollar of growth in assets. This quantitative prediction should not hold for the relatively small number of firms which access external equity. We test these predictions with a panel of more than 1, 600 small firms and find that the growth of most firms is constrained by internal finance. Our results have implications for several different research literatures, including models of firm growth.